Dialektika Ẓāhir Bāṭin dan Produksi Makna Ishārī dalam Tafsir al-Baḥr al-Madīd - Isnaini, Subi Nur; Adim, Fauzan (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2021)
Abstract: This article examines the sufi Qur’anic exegesis of al-Baḥr al-Madīd on how is the dialectic of ẓāhir and bāṭin shaping a new meaning of the Qur’an. By using descriptive analysis, this article argues that Ibn ‘Ajībah is one of the authoritative sufi scholars who tends to interpret the Qur’an with regards to the balanced hermeneutics of the exoteric (ẓāhir) and the esoteric (bāṭin) meanings of it. The existence of the esoteric meaning should not violate the exoteric interpretation. According to Ibn ‘Ajībah, the exoteric meaning becomes the initial basis for the birth of the esoteric interpretation. Related to the symbolic (ishārī) interpretation, it is quite visible when Ibn ‘Ajībah interprets the term al-arḍ in his exegesis. This article finds that there are at least four allegorical meanings with representative of Sufism presented by Ibn ‘Ajībah in terms of al-arḍ, namely: qalb (heart), ashbāḥ (body), nafs (soul), and arḍ al-ḥikmah (wisdom). The four meanings presented are diametrically different from the meaning of arḍ in its linguistic sense which is generally perceived by the most Qur’anic commentators as the ‘earth’ inhabited by humans.